Perancangan Aplikasi Otomatisasi Jual Beli Aset Kripto Menggunakan Metode Relative Strength Index (Studi Kasus ETH/USDT pada binance.com) - Rio Fajar Saputra; Hardiansyah (CV. Multi Kreasi Media, 2023)
Virtual Currency technology will allow people to buy, trade and invest without the intervention of banks or other financial institutions, one of which is Cryptocurrencies. Cryptocurrency trading is starting to get busy, where traders carry out trading activities by uniting market prices continuously. To make trading easier, we need an application that automatically performs trading activities. Automated Buying and Selling of Crypto Assets will use the Relative Strength Index (RSI) method or technical analysis. The results obtained indicate that the Automated Buying and Selling of Crypto Assets application can provide convenience for traders in conducting trades. However, this Crypto Asset Trading Automation application does not guarantee that it will always provide profits due to highly volatile price movements.